Comparison between Oral Nifedipine and Intravenous Labetalol in Managing Severe Preeclampsia: Oral Nifedipine and Intravenous Labetalol in Managing Severe Preeclampsia - Siddiqua, Ayesha; Sabir, Anila; Siddique, Nadia; Bakht, Faraz; Rauf, Hina; Zafar, Hania (Pakistan Journal of Health Sciences, 2025)
Hypertensive disorders contribute to significant maternal morbidity and mortality in pregnancy. Immediate treatment is required to avoid serious complications. Objectives: To compare the mean time taken to achieve the target BP with oral nifedipine versus intravenous labetalol in patients with severe preeclampsia. Methods: This quasi-experimental study was conducted at Lady Willington Hospital, Lahore, over six months after taking approval from CPSP, involving 100 patients diagnosed with severe preeclampsia. Participants were divided into two equal groups: Group oral nifedipine and IV labetalol. Study outcome time taken to reach target BP <140/90 mmHg was compared among groups using an independent sample test, with a p-value≤ 0.05 as significant. Results: Target BP was achieved earlier at 43.96 ± 5.93 minutes with oral nifedipine compared to IV labetalol at 48.60 ± 6.80 minutes (p<0.001). Conclusions: It was concluded that the findings strongly support the use of nifedipine as a more effective option for rapidly lowering blood pressure compared to labetalol. Its faster onset of action makes it the preferred choice for achieving timely blood pressure control in patients with severe preeclampsia.